EKONOMI KREATIF DI ERA PANDEMI COVID 19 DENGAN MENINGKATKAN KERAJINAN PAYUNG KERTAS KALIBAGOR SEBAGAI HASIL BUDAYA KERAJINAN BANYUMAS - Andriani, Ana; Kertopati, R. Benny Bijarnako; Harmianto, Sri (Community Services and Social Work Bulletin, 2021)
: Umbrellas as a medium for meeting human needs are certainly very familiar. In this condition, it can be seen that umbrellas are adaptive living equipment, so that even umbrellas need to be seen as 'symbolic objects' that have various meanings for their users. Umbrellas in Java have long historical roots dating back to the 1950s. The initial function of the umbrella was as body protection from hot or rainy weather, but then the umbrella transformed into other functions such as in art, death and became symbols of nobility. Kalibagor is one of the sub-districts located in Banyumas district. Many home industries for paper umbrellas are made directly by the community. The raw materials for this paper umbrella are paper and wood. Even the umbrellas are painted, there is no machine intervention. As the years change, the times change, technology exposure is unavoidable for umbrella craftsmen. The existence of modern umbrellas made from synthetics and manufactured iron handles, makes consumers abandon hand-assembled umbrellas. This paper will discuss how this Kalibagor paper umbrella craft can survive and continue to live in the modern era, especially during the COVID-19 pandemic to continue to support the family and surrounding community.